Azide, water and adipate as bridging ligands for Cu(II): Synthesis, structure and magnetism of (μ4-adipato-κ-O)(μ-aqua)(μ-azido-κN1, N1)copper(II) monohydrate. (15th October 2016) - Setifi, Zouaoui; Ghazzali, Mohamed; Glidewell, Christopher; Pérez, Olivier; Setifi, Fatima; Gómez-García, Carlos J.; Reedijk, Jan
Graphical abstract: The first compound with a triple symmetric water/azide/carboxylato bridge is a Cu(II) ferromagnetic chain with a metamagnetic behavior that has been structurally and magnetically characterized. Abstract: The synthesis, characterization, single crystal structure and magnetic properties of the compound [(CuN3 (OH2 ))2 (adp)] n (1 ) are presented, in which adp stands for the adipate(2−) anion. This compound consists of layers containing chains of six-coordinated Cu(II) ions; the chains are connected by μ4 -adipate anions. The magnetically interesting part of the compound is the Cu(II) chain, built from 3 bridging ligands, i.e. a water ligand, an azide anionic ligand bridging by using a terminal N atom to connect 2 Cu(II) ions, and one symmetrically bridging carboxylato group of adipate; the other end of the tetradentate adipate anions symmetrically connect the chains, forming the layers. From the magnetic point of view the compound is considered as a Cu(II) chain with a quite unusual, symmetrical water bridge, the μ-syn-syn carboxylate and the μ-N3 bridge. The bridging water also hydrogen bonds to a terminal N of a nearby azido ligand. Magnetic susceptibility measurements show that1 presents moderate ferromagnetic intrachain interactions ( J chain = +38.4 cm −1 ) with a metamagnetic behaviour for the inter-chain interaction with a critical field of 0.7 T.